Analisis Pemahaman Mahasiswa Perbankan Syariah Terhadap Akad Musyarakah Mutanaqishah - Janes Kurnia Hadi; Miti Yarmunida; Evan Stiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT This study aims to determine the level of understanding of Islamic Banking students class 2018 Faculty of Economics and Islamic Business Fatmawati Sukarno Bengkulu State Islamic University towards the musyarakah mutanaqisah contract. This type of research is field research, using a qualitative approach. This research was conducted in June 2022, at the Faculty of Economics and Islamic Business, UINFAS Bengkulu. Sources of data used are primary data sources obtained directly from students of the Faculty of Economics and Islamic Business who serve as respondents, and secondary data sources come from books, as well as other literature related to research. Data collection techniques used are Observation, Interview, and Documentation. The results of this study are to determine student understanding, researchers are guided by three categories, namely the ability to translate, the ability to interpret, and the ability to extrapolate. Based on these three categories, the level of understanding of the 8th semester students of the Islamic Banking study program at UINFAS Bengkulu about the musyarakah mutanaqisah contract is in a good percentage, many respondents easily translate each question given using their own language based on the material that has been given during lectures. Besides being able to translate, respondents are also able to interpret the material being asked, and are able to extrapolate. Keywords : understanding, sharia banking, musyarakah mutanaqisah